Evaluation of source–sink manipulation through defoliation treatments in promising bread wheat lines under optimal irrigation and rainfed conditions - Ershadimanesh, Khosro; Siosemardeh, Adel; Hoseeinpanahi, Farzad (Frontiers in Agronomy, 2024)
The source–sink (S-S) ratio during the grain-filling period is crucial for wheat crop yield. The aim of this study was to investigate the relative sensitivity of grain yield in response to treatments of S-S ratio changes to determine the extent of S-S limitation during grain filling in modern wheat genotypes. The S-S manipulation treatments included four levels: check (CH), removal of flag leaf (RFL), removal of all leaves (RAL), and removal of the upper half of the spikes (RHS). The results showed significant differences between genotypes (pb< 0.001%) in all traits. Drought stress decreased grain weight per spike (GWS) (g) and grain yield (GY) (kg/ha) by 18% and 25%, respectively. The average reduction in GWS under irrigation and rainfed conditions was 8.25% and 6.71% for RFL and 12.25% and 11.15% for RAL, respectively. By RFL and RAL, increasing the remobilization from the stem and spike straw helped to reduce the effects of source limitation. Also, by RHS, the reduction in photosynthetic materials production in both conditions was only equivalent to 38% and 29% of the expected values, respectively, which shows the presence of strong sinks in vegetative organs (stem and spike) compared to grains. Vegetative organs seem to have a larger sink for the uptake of photosynthetic materials than grains when the source–sink ratio increases. However, high-yield genotypes showed more severe source limitation, while low-yield genotypes showed more relative sink limitation. Overall, to increase the yield potential in high-yielding genotypes, photosynthetic sources and sinks in low-yielding genotypes should be improved.